Relación entre el estado nutricional y el rendimiento académico en los escolares de la Institución Educativa nº 0655 "José Enrique Celis Bardales, Mayo •Diciembre 2011 - Arévalo Fasabi, Janina (2011)
Tbe study, entitled "relationship between nutritional status and academic performance in students of the educational institution. Jose Enrique Ceils Bardales." Tarapoto, may - December 2011 ", was a study of correlation type with quantitative approach, where we plateamos us the aim of knowing the re1ationship between nutritional status and academic performance of the students of the educationa1 :institution Jose Enrique Ceils Barda1es, located in the District of Tarapoto. The sample was comprised of 63 students, three sections of the fifth grade (where are taken randomly to 11 students from each section); and three sections of the sixth grade of primary (where is also taken randomly to 10 students from eacb section). Were both collected data using a registration form in order to determine the nutritional status and academic performance, proceeded despite and carving to determine BMI and be able to classify the nutritional status of schoolchildren, and requested notes academic each student selected for the third quarter. Results notes that the nutritional status of schoolcbildren of the I. E. Jose Enrique Ceils Bardales; the 42.9 % had low birth weight., the 39.7% a nutritional status within normal parameters, 15.9 % were overweight and only 1.6% had obesity, indicate the level of school performance than the 57.1% presented hígh academic performance in the course of art, while other subjects presented in academic performance regu1arly. To relate the nutritional status and school performance by school subjects, notes that the 42.9% have a nutritional status with low birth weight, and in turn presented academic performance regular in all their subjects (Science and environment. íntegrated communication. physical education. religious education, mathematics) with the exception of tbe subject of art. While the 39,7% presents a nutritional status with in normal parameters, also regular academic performance, and 15.9 per cent of schoolclúldren who were overweight. also presented a regular academic performance, and only 1.5% of scboolcbildren who presented obesity also presented academic performance regularly. To make the correlation between nutritional status and academic performance by subjects, it was noted that there was no significant relationship between the two variables, so it can be concluded that nutritional state does not have a significant relationship with academic achievement.